Mycorrhization stimulant based in formononetin associated to fungicide and doses of phosphorus in soybean in the cerrado (Bioscience Journal, 2015)
Arbuscular mycorrhizal fungi (AMF) are obligatory biotrophics, which complicates the feasibility of producing inoculants. Thus, the discovery of substances capable of stimulating mycorrhizal colonization, as the isoflavone formononetin emerges as a promising alternative to explore the benefits of AMF native soil in extensive crops. The objective of this study was evaluate the application of the isoflavone formononetin (7-hydroxy-4'-methoxy isoflavone), fungicide application via seed in Cerrado soil in no-tillage system and fertilized with two doses of phosphorus in soybean under field and controlled conditions. In the field experiment treatments there were three levels of formononetin (0, 0.5 and 1.0 mg/seed Formononetin), in the absence and presence of fungicide (Carbendazim + Thiram commercial mix) applied to seeds and two doses of phosphorus (100 % and 33% of the recommended fertilization). The study was conducted until the maturation of soybeans. The greenhouse conditions experiment was implemented with the same treatments used in the field study and the flowering stage of the soybean plant was simulated water stress for 10 days, returning to normal irrigation to harvest the grain. Applying formononetin stimulated increased mycorrhizal colonization, number of nodules, vegetative growth and soybean production in the greenhouse and in the field and contributes to attenuate the negative effect of the fungicide Carbendazim + Thiram in soybean reflecting increased soybean production and adequate supply of soil phosphorus and high density of propagules of natives AMF contributed to reduce the benefits of stimulating mycorrhizal (formononetin) in the studied soil.